6 - Liberté académique en question : contribution à la problématisation d’une notion à partir du cas estudiantin au Sénégal - Abdoulaye Guèye, (Journal of Higher Education in Africa, 2011)
Academic freedom at issue: contribution to problematizing a notion from the Senegalese experience of students. Throughout its development, the aca- demic institution is faced with the issue of liberty. Countries with a long tradition of higher education are still experiencing this problem today. A relevant literature is devoted to this issue, However, it is mostly character- ized by what I would the ‘‘externalist and political approach’’. For research- ers to ask the the question of academic liberty is to account for the confron- tation between two groups: the community of scholars ( i.e. academics, stu- dents and students) and the non-academic world defined by its political actors (the national and regional political leaders, etc.). Thus, imprisonments and assassinations of academics by political leaders or oppositional fac- tions (e.g. the FIS and the GIA in Algeria) are sufficiently documented. This approach is somewhat reductionist, although the authoritarian characteris- tic of many African (government) regimes could explain that. As such, it offers a homogenous view of the academic institution. Yet, like any field, this institution is characterized by high diversity both in the status of the actors it hosts and the stakes that pervades it. The purpose of this article is to analyze the issue of academic freedom from the perspective and the experi- ence of students.